Identifying Junior High School Student’s Learning Needs and Challenges in Science Education - Wiwit Yuli Lestari; Hertien Koosbandiah Surtikanti; Taufik Rahman; Riandi Riandi (STAI Hubbulwathan Duri, 2025)
Understanding students’ needs in science education is essential for improving teaching strategies and learning outcomes. This study investigates students’ preferences regarding teaching methods, learning materials, and supplementary education outside school.The study employed a descriptive research design involving 119 students and 28 teachers from seven randomly selected schools in Ciamis. Participants had prior experience with online learning. Data were collected through questionnaires and interviews and analyzed quantitatively using percentage-based analysis.Findings reveal that 95% of students enjoy learning science due to its real-life relevance. Approximately 79% favor practical-based learning methods, citing ease of understanding and increased engagement, while 21% reported disinterest or discomfort with practical activities. Face-to-face instruction was preferred by 88.2% of students for its interactive benefits, though 3.57% felt teachers did not sufficiently involve them, potentially limiting critical thinking development. Regarding learning materials, 79.8% of students confirmed material availability, preferring those that are visual, durable, and easy to understand. Only 7.6% of students pursued additional lessons, primarily to enhance comprehension or complete assignments.These findings highlight students' inclination toward interactive and visually supported science instruction. Barriers such as limited engagement and lack of exposure to practical learning should be addressed to foster a more effective educational experience.Identifying and addressing students’ preferences in science education can inform more effective instructional approaches and resource development.